2007
DOI: 10.1007/s00401-007-0299-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial alterations in dorsal root ganglion cells in sporadic amyotrophic lateral sclerosis

Abstract: Little information is available regarding the morphological changes in the mitochondria in amyotrophic lateral sclerosis (ALS). In particular, mitochondrial changes in dorsal root ganglion cells have not yet been examined. We therefore conducted an electron microscopic examination of the mitochondria in dorsal root ganglion cells in 11 sporadic ALS patients, and 12 age-matched, non-neurological control individuals in order to determine whether or not they are affected in ALS. In both the controls and ALS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…The righting reflex may also be a measure of declining proprioception. Evidence suggests the dorsal root [102], dorsal root ganglia [102], [108][110], dorsal funiculus [102], Clarke's nuclei [103], [109], [111], [112] and spinocerebellar tract [103], [109], [111]–[113], the regions of the spinal cord responsible for processing proprioception, may be affected in humans with ALS [103], [108][112] and animal models of ALS [102], [113], however some researchers failed to ascertain this association [113]. It is important to note that the magnitude of diminished proprioception and muscle loss may be different depending on the time used as the cutoff for the righting reflex, with greater atrophy of motor neurons occurring when longer cutoffs are used [113].…”
Section: Discussionmentioning
confidence: 99%
“…The righting reflex may also be a measure of declining proprioception. Evidence suggests the dorsal root [102], dorsal root ganglia [102], [108][110], dorsal funiculus [102], Clarke's nuclei [103], [109], [111], [112] and spinocerebellar tract [103], [109], [111]–[113], the regions of the spinal cord responsible for processing proprioception, may be affected in humans with ALS [103], [108][112] and animal models of ALS [102], [113], however some researchers failed to ascertain this association [113]. It is important to note that the magnitude of diminished proprioception and muscle loss may be different depending on the time used as the cutoff for the righting reflex, with greater atrophy of motor neurons occurring when longer cutoffs are used [113].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown some similar changes in DRG neurons, including cytoplasmic vacuolation, and mitochondrial swelling ( Figure 5). In this connection, it is worth noting that a previous study showed increased number of inclusion bodies in DRG neurons of sporadic ALS patients (Sasaki et al, 2007). The VR and DR fibers exhibited Wallerian-like degeneration: axon damage, myelin degeneration, and phagocytic cell (macrophages) infiltration into the tissues (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial abnormalities are observed in the CNS of sporadic ALS subjects. In dorsal root ganglion cells, ALS subjects have a higher number of mitochondrial inclusions, which appear to consist of aggregates within the cristae and intermembrane space [279]. Further studies showed abnormal mitochondrial morphology and aggregation of mitochondria in the anterior horn of the spinal cord [280].…”
Section: Mitochondrial Medicine and Alzheimer’s Diseasementioning
confidence: 99%